PELUANG DIGITAL MARKETING DALAM KEBANGKITAN PARIWISATA DI INDONESIA - Irra Chrisyanti Dewi; Moses Soediro; Michael Ricky Sondak (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
The purpose of this study is to explore digital marketing opportunities for tourism in Indonesia, which is motivated by the development of tourism in Indonesia, especially the increase in tourist visits and statistics in the digital era. Integrative literature review is the method used in this research and content analysis to review digital marketing and tourism in Indonesia. The findings from this study are that digital media, content, and mobile advertising are one of the trends in digital marketing. Thus, tourism activists in Indonesia have the opportunity to market their products digitally. For further research, you can explore quantitative and qualitative methods about the digital marketing phenomenon in finding tourism in Indonesia. Abroad, they have implemented digital marketing where they have utilized digital media and created creative content to manage the digitization of marketing activities in the tourism sector.